Hierarchical Chemical Bonds Contributing to the Intrinsically Low Thermal Conductivity in α‐MgAgSb Thermoelectric Materials. (28th October 2016) - Ying, Pingjun; Li, Xin; Wang, Yancheng; Yang, Jiong; Fu, Chenguang; Zhang, Wenqing; Zhao, Xinbing; Zhu, Tiejun
Abstract : Understanding the lattice dynamics and phonon transport from the perspective of chemical bonds is essential for improving and finding high‐efficiency thermoelectric materials and for many applications. Here, the coexistence of global and local weak chemical bonds is elucidated as the origin of the intrinsically low lattice thermal conductivity of non‐caged structure Nowotny–Juza compound, α‐MgAgSb, which is identified as a new type of promising thermoelectric material in the temperature range of 300–550 K. The global weak bonds of the compound lead to a low sound velocity. The unique three‐centered MgAgSb bonds in α‐MgAgSb vibrate locally and induce low‐frequency optical phonons, resulting in "rattling‐like" thermal damping to further reduce the lattice thermal conductivity. The hierarchical chemical bonds originate from the low valence electron count of α‐MgAgSb, with the feature shared by Nowotny–Juza compounds. Low lattice thermal conductivities are therefore highly possible in this series of compounds, which is verified by phonon and bulk modulus calculations on some of the compositions. Abstract : A coexistence of hierarchical weak bonds in non‐caged compound of α‐MgAgSb leads to low thermal conductivity. The weak bondings are found in other typical Nowotny–Juza compounds with low valence electrons, and low lattice thermal conductivities are expectede. Future studies about Nowotny–Juza compounds are therefore encouraged in order to find compounds with low thermal conductivity and high thermoelectric efficiency.